Pengaruh Gradasi Agregat terhadap Kuat Tekan dan Permeabilitas pada Beton Porus - Hamzah, Muhammad Syafrie; Rochmah, Nurul (Jurnal Sains dan Teknologi (JSIT), 2025)
Pervious concrete is designed with open pores to allow water to flow through the concrete structure, unlike conventional concrete which is impermeable. This concrete is effective in stormwater management and groundwater recharge, making it an ideal choice for urban sidewalks. This study aims to analyze the effect of aggregate gradation on the compressive strength, permeability, porosity, and absorption of pervious concrete. The method used follows the ACI 522 R-10 mix design. The test results show that gradation A (5-10 mm) has the best compressive strength of 9.24 MPa, the lowest permeability of 0.23 cm/s, porosity of 23.57%, and absorption of 12.96%. Gradation B (10-15 mm) results in a compressive strength of 7.20 MPa, permeability of 0.38 cm/s, porosity of 27.81%, and absorption of 7.86%. Meanwhile, gradation C (15-20 mm) shows the lowest compressive strength of 5.92 MPa, permeability of 0.30 cm/s, the highest porosity of 36.31%, and absorption of 9.80%. Larger aggregate gradation increases permeability and porosity but decreases compressive strength.